Modul Elektronik Berbasis Project Based Learning (PjBL) pada Pembelajaran Manajemen Proyek - Widyastuti, Rini (AI Society & STMIK Indonesia, 2024)
The research started with the problem of project management learning, where learning uses modules that do not involve active students and independent learning, namely there are no electronic modules that attract students, the material is difficult to understand, problems are not carefully analyzed, so that at the end of the lecture there are still difficulties in managing projects. The aim of this research is to produce a valid and practical PjBL-based electronic module. The research method uses research and development by applying the 4D model, namely define, design, develop, and disseminate. The validity sheet and practicality questionnaire are the instruments of this research. The data analysis technique is descriptive analysis with a percentage of validity and practicality tests. Validity analysis through design and material experts, as well as practicality was carried out by 17 PTIK students. The research results showed that the electronic module was declared valid by the validator at 81% from the aspects of language, presentation, writing, content and programming. The results of the practicality test with practical criteria are 80% seen from the aspects of language, benefits, use and appearance. So that electronic modules can be used according to students' learning needs.